Role of traditional Chinese medicine in ameliorating mitochondrial dysfunction via non-coding RNA signaling: Implication in the treatment of neurodegenerative diseases - Cai, Zhongdi; Liu, Mimin; Zeng, Li; Zhao, Kaiyue; Wang, Chenyu; Sun, Ting; Li, Zhuorong; Liu, Rui (Frontiers in Pharmacology, 2023)
Neurodegenerative diseases (NDs) are common chronic disorders associated with progressive nervous system damage, including Alzheimer's disease, Parkinson's disease, and Huntington's disease, among others. Mitochondria are abundant in various nervous system cells and provide a bulk supply of the adenosine triphosphate necessary for brain function, considered the center of the free-radical theory of aging. One common feature of NDs is mitochondrial dysfunction, which is involved in many physiopathological processes, including apoptosis, inflammation, oxidative stress, and calcium homeostasis. Recently, genetic studies revealed extensive links between mitochondrion impairment and dysregulation of non-coding RNAs (ncRNAs) in the pathology of NDs. Traditional Chinese medicines (TCMs) have been used for thousands of years in treating NDs. Numerous modern pharmacological studies have demonstrated the therapeutic effects of prescription, herbal medicine, bioactive ingredients, and monomer compounds of TCMs, which are important for managing the symptoms of NDs. Some highly effective TCMs exert protective effects on various key pathological features regulated by mitochondria and play a pivotal role in recovering disrupted signaling pathways. These disrupted signaling pathways are induced by abnormally-expressed ncRNAs associated with mitochondrial dysfunction, including microRNAs, long ncRNAs, and circular RNAs. In this review, we first explored the underlying ncRNA mechanisms linking mitochondrial dysfunction and neurodegeneration, demonstrating the implication of ncRNA-induced mitochondrial dysfunction in the pathogenesis of NDs. The ncRNA-induced mitochondrial dysfunctions affect mitochondrial biogenesis, dynamics, autophagy, Ca2+ homeostasis, oxidative stress, and downstream apoptosis. The review also discussed the targeting of the disease-related mitochondrial proteins in NDs and the protective effects of TCM formulas with definite composition, standardized extracts from individual TCMs, and monomeric compounds isolated from TCM. Additionally, we explored the ncRNA regulation of mitochondrial dysfunction in NDs and the effects and potential mechanisms of representative TCMs in alleviating mitochondrial pathogenesis and conferring anti-inflammatory, antioxidant, and anti-apoptotic pathways against NDs. Therefore, this review presents an overview of the role of mitochondrion-related ncRNAs and the target genes for TCM-based therapeutic interventions in NDs, providing insight into understanding the “multi-level compound-target-pathway regulatory” treatment mechanism of TCMs